2015
DOI: 10.1111/weng.12174
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Englishes in India

Abstract: With the help of a survey building on 13 bipolar pairs arranged on a six‐point semantic differential scale, the present paper studies Indian English speakers’ attitudes towards their local variety Indian English contrastively by simultaneously examining their attitudes towards American English, British English and Sri Lankan English. The results show that although Indian speakers of English display a positive attitude towards Indian English, which is most pronounced with the group of young female informants po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 25 publications
5
36
0
Order By: Relevance
“…Despite the overall resistance and negative attitudes shown by the study participants towards EIL/EFL at first, they later-after I had explained to them IEL/EFL-showed some kind of readiness to try out this kind of English as they viewed it as 'easy' and could work out well for developing their communication skills. Such degree of positive attitude and acceptance towards learning of EIL/ELF resonates with some previous studies (e.g., Ahn, 2014;Bernaisch & Koch, 2016) on attitudes of teachers and learners towards local varieties of English due to its high degree of intelligibility and easiness. Such findings suggest that teachers and learners should not shy away from trying out such non-standard mainstream variety of English.…”
Section: Conclusion Implications and Recommendations For Tesolsupporting
confidence: 89%
“…Despite the overall resistance and negative attitudes shown by the study participants towards EIL/EFL at first, they later-after I had explained to them IEL/EFL-showed some kind of readiness to try out this kind of English as they viewed it as 'easy' and could work out well for developing their communication skills. Such degree of positive attitude and acceptance towards learning of EIL/ELF resonates with some previous studies (e.g., Ahn, 2014;Bernaisch & Koch, 2016) on attitudes of teachers and learners towards local varieties of English due to its high degree of intelligibility and easiness. Such findings suggest that teachers and learners should not shy away from trying out such non-standard mainstream variety of English.…”
Section: Conclusion Implications and Recommendations For Tesolsupporting
confidence: 89%
“…Now, English has lost its position as the official language in Indian society and recently has served as a lingua franca (ELF) which is salient in terms of research efforts and status recognition (Kachru, 1995, p.305). The Indianization of English (Kachru, 1986;Bernaisch & Koch, 2016) goes beyond the linguistic levels and symbolizes Indian local culture, as mentioned by Kachru (1986) Interaction of social, cultural and linguistic features in the teaching of English will be different between teachers and contexts. This investigation brings to light the ways in which English teachers in Outer and Expanding circles identify with different varieties of English.…”
Section: The Historical Background Of English In Iran and Indiamentioning
confidence: 99%
“…For South Asia, it has been shown that Indian as well as Sri Lankan speakers of English give the least positive evaluation to their respective neighbor variety (cf. Bernaisch and Koch 2016), which may present an attitudinal hurdle to epicentral influences. Still, the relevance of attitudes for epicentral influence to take effect seems closely connected to the degree of speaker awareness of the feature that may be spread in an epicentral fashion.…”
Section: Linguistic Epicenters In Asia and Their Explorationmentioning
confidence: 99%